Physico-chemical and combustion analyses of bio-briquettes from biochar produced from pyrolysis of groundnut shell - Ayodeji Rapheal, Ige; Cosmos Moki, Elinge; Muhammad, Aliyu; Mohammed, Gwani; Gusau Hassan, Lawal; Umar BirninYauri, Abubakar (International Journal of Advanced Chemistry, 2021)
The initiative of using biomass as a preference source of energy is vindicated by its availability, abundance, easy accessibility and its eco-friendly nature. This therefore calls for the conversion of agricultural wastes to usable form. This study is aimed to investigate the physicochemical and combustion properties of briquettes obtained from pyrolyzed biochar of groundnut shell. The groundnut shell biochar briquette bonded with cassava starch as binder were molded and analyzed. Proximate analysis, ultimate analyses, Scanning electron microscopy (SEM), Calorific values, density and compressive strength, among other properties, were determined for the fabricated briquettes. A high heating value of 45.20 MJ/Kg was recorded for groundnut shell biochar briquette compared to 25.20 MJ/Kg of raw groundnut shell briquette. While the ash contents of 5.12 % and 6.40 % were recorded for raw groundnut shell briquette and groundnut shell biochar briquette respectively. It took groundnut shell biochar briquette approximately 10 minutes to boil 1000 cm3 of water, while raw groundnut shell briquette boiled same quantity of water in 20 minutes. The finding of this study shows that the biochar obtained from the pyrolysis of groundnut shell is suitable for fuel briquette production.Â Â